MEDIASI DISIPLIN DAN BEBAN KERJA DI PT SIRTANIO ORGANIK INDONESIA - M. Richo Andreansyah; Widakdo Danang SWPJ; Aji Ardito Atmaka (Politeknik Negeri Banyuwangi Jl. Raya Jember km. 13 Labanasem, Kabat, Banyuwangi, Jawa Timur (68461) Telp. (0333) 636780, 2022)
This study aims to determine the effect of work discipline and workload on employee performance at PT Sirtanio Organik Indonesia, Research data collection techniques used questionnaires. The sampling method used is a non-probability sample with a total sampling technique. The result of the t-test and f-test analysis showed that the variable of work discipline (X1) and workload (X2)had a positive and significant effect on employee performance partially or simultaneously. The R square value of 0,644 indicated that the magnitude of the influence of work discipline and workload on employee performance is 64,4% and the remaining 35,6% is influenced by other variable.